Influence of skeletal muscles on the risk of falling in old age - Schöne, Daniel; Freiberger, Ellen; Sieber, Cornel (Internist, 2017)
Falls in older adults are a major public health problem, affecting 1 in 3 persons aged 65 and over at least once a year. Consequences of falling include death, injuries, fear of falling, and subsequent loss of independence. The age-related loss of muscle mass and function (sarcopenia) as well as muscle strength are markers of the frailty syndrome. In addition, they are associated with physical function and are a risk factor for falling. Older adults should be screened for falls at least annually. If evaluated as at-risk, a comprehensive falls assessment should be conducted to determine an individual's risk profile. Physical exercise with balance and strength training play a key role in the prevention and management of functional decline and fall risk. Multifactorial interventions are indicated in at-risk individuals. In sarcopenic individuals, sufficient intake of protein must be taken into account and supplementation in combination with exercise appears to be useful.